ANALISIS SIKAP DAN MOTIVASI BELAJAR ANTARA PEMBELAJARAN LANGSUNG DAN PEMBELAJARAN KOPERATIF PADA SISWA KELAS VII MTS NEGERI 1 KOTABARU - Rahmi Yuliana; Agus Syarifuddin (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2018)
The research located in MTS Negeri 1 Kotabaru. This type of research is a research experiment involving two groups who were given different treatment. This study aims to determine whether direct learning and cooperative learning have an influence on attitudes and motivation to learn mathematics in a Class VII students of MTS Negeri 1 Kotabaru. The study population was class VII MTS Negeri 1 Kotabaru in odd semesters 2017/2018 and 2 classes were randomly selected as sample class. Techniques of data analysis performed using descriptive and inferential statistical techniques. The results showed that: (1) Students taught in the control class showed positive learning attitudes towards the application of direct learning models with an average score of 93.13. (2) Students taught in the control class show positive learning motivation towards the application of direct learning models an average score of 63.85. (3) Students taught in class discourse learn positive attitudes towards the application of cooperative learning models. with an average score of 93.13. (4) Students taught are classified as one of the teachers who learn positively about the application of cooperative learning models. with an average score of 70.34. (5) Both learning models that are universal towards student learning attitudes and manners towards student learning speed, but from the results of homogeneity test data analysis shows that from both learning models have a value of F = 0.422 (p = 0.518) because p with the value of Î± ( 0.05) it can be seen that there is no variant of data on learning attitudes data, but on the average the average student who studies class is more effective. Likewise with learning mathematics with a value of F = 2.252 (p = 0.138) because p is greater than the value of Î± (0.05) it can be seen that there is no difference in variants of learning motivation data, but on the average experimental class learning is more positive and learning control class math students. Keyword: Direct learning model, cooperative learning model, attitude and motivation learning.